Researcher Li-Ming MA: Contributions to systematic acarology and entomology - Lin, Jian-Zhen (Zootaxa, 2022)
This paper provides a brief biography of researcher Li-Ming Ma (1935–2021), who was a Chinese systematic acarologist and entomologist. He published 464 papers during his professional life (106 papers during working years, 358 papers after his retirement). During 1957–2021, he established two new genera, one new subgenus, 342 new species and three new subspecies of arthropods, which are catalogued here. The information provided includes genus and species names, type data, hosts, location, type deposition and reference list. Some of the types of 126 species were transferred from their original deposition to IZAS (Institute of Zoology, Academia Sinica, Beijing, China).